PENGARUH OLAHRAGA AEROBIK INTESITAS MODERAT DI RUMAH TERHADAP KEBUGARAN KARDIORESPIRASI DI MASA PANDEMI COVID - 19 PADA MAHASISWA FK UMSU - QORY AULIA DANA LUBIS; GUSBAKTI RUSIP (JURNAL ILMIAH MAKSITEK, 2021)
The Coronavirus disease (COVID-19) pandemic is still ongoing today. Health protocols are in place and students are advisedto stay at home. The limitation of activities due to this pandemic has a negative impact on health due to physical inactivityand secondary behaviour. Cardiorespiratory fitness (CRF) is one of the vital indicators that describes an individual's overallhealth. Aerobic exercise has previously been shown to increase CRF. This study was a pre-test and post-test control groupdesign. The subjects in this study used consecutive sampling as many as 32 FK UMSU students. The intervention groupperformed moderate intensity aerobic exercise at home for 4 weeks, while the control group was not given any intervention.The research instrument used the Astrand-ryhming Step Test method to measure the VO2max value. Statistical analysisused the Wilcoxon test and the Mann-Whitney test. There was an average CRF increase of 2.4% after moderate intensityaerobic exercise at home and a decrease in mean CRF of 18.9% in the control group. Statistically, the increase in CRF in theintervention group was not significant (p> 0.05). The Mann-Whitney test also showed insignificant results (p> 0.05). There isno effect of moderate intensity aerobic exercise at home on cardiorespiratory fitness during the COVID-19 pandemic amongFK UMSU students.